Reseña de: Spiteri, Mevrick, The Houses of Baroque Valletta 1650-1750. Property redevelopment from records of the Officio delle Case: socio-economic reflections on civil buildings - Molina , Álvaro (Espacio Tiempo y Forma. Serie VII, Historia del Arte, 2022)
Reseña de: Spiteri, Mevrick, The Houses of Baroque Valletta 1650-1750. Property redevelopment from records of the Officio delle Case: socio-economic reflections on civil buildings. Valletta, Midesea Books, 2021. ISBN: 978-99932-7-814-6, 320 pp.